A molecularly imprinted polymer based on a novel polyaniline–zinc sulfide nanocomposite for electrochemical detection of trimethylamine N-oxide. Issue 10 (21st September 2022) - Verma, Damini; Sajwan, Reena K.; Lakshmi, G. B. V. S.; Kumar, Anil; Solanki, Pratima R.
Abstract : Illustration of the MIP based electrochemical sensing platform of TMAO. Abstract : The generation of gut microbiota-derived trimethylamine N -oxide (TMAO) from the metabolism of dietary l -carnitine and choline is associated with a high risk of major adverse effects on humans. For this purpose, cheap, rapid, highly sensitive, and accurate electrochemical sensors are needed to detect TMAO in real samples clinically. Thus, a sensor showing all these features is developed based on a molecularly imprinted technique and characterized using X-ray diffraction, scanning electron microscopy, UV-Visible spectroscopy, and Fourier transform infrared spectroscopy in this study. The MIP sensor is fabricated using a novel nanocomposite (PANI–ZnSNPs) that comprises a polyaniline polymer (PANI) and zinc sulphide nanoparticles (ZnSNPs) that serve as a receptor and are deposited on an indium tin oxide (ITO) coated glass substrate using the electrophoretic deposition technique. The chemical interaction responsible for bonding between the gut metabolite TMAO and PANI–ZnSNPs is hydrogen bonding occurring between the oxygen atoms of N -oxides and NH of PANI on the addition of TMAO concentrations resulting in a decrement in the current (after 10 min of incubation time) and electro-activity of the sensor. The developed MIP sensor exhibited a linear range from 5 μM to 180 μM having a limit of detection of 4.35 μM. Moreover, the sensor showed a high sensitivity of 0.276 μA μM −1 cm −2 ( R 2 = 0.984), as well as relative standard deviation (RSD) values for selectivity analysis, which were found to be in the range of 3.12% to 7.50% for several interfering agents. It also showed promising results related to reproducibility (RSD = 4.34%), repeatability (RSD = 0.08%), and the potential to determine TMAO in spiked urine samples with acceptable RSD, as well as % recovery values ranging from 96.67–110.58% and 0.55–7.11%, respectively. The current strategy is potent and opens a new pathway for developing fast diagnostic tools for TMAO detection and other metabolites.